Women's perceptions of factors influencing their food shopping choices and how supermarkets can support them to make healthier choices - Preeti Dhuria; Wendy Lawrence; Sarah Crozier; Cyrus Cooper; Janis Baird; Christina Vogel (BMC, 2021)
Abstract Objectives To examine women's perceptions of factors that influence their food shopping choices, particularly in relation to store layout, and their views on ways that supermarkets could support healthier choices. Design This qualitative cross-sectional study used semi-structured telephone interviews to ask participants the reasons for their choice of supermarket and factors in-store that prompted their food selections. The actions supermarkets, governments and customers could take to encourage healthier food choices were explored with women. Thematic analysis was conducted to identify key themes. Setting Six supermarkets across England. Participants Twenty women customers aged 18-45 years. Results Participants had a median age of 39.5 years (IQR: 35.1, 42.3), a median weekly grocery spend of £70 (IQR: 50, 88), and 44% had left school aged 16 years. Women reported that achieving value for money, feeling hungry, tired, or stressed, and meeting family members' food preferences influenced their food shopping choices. The physical environment was important, including product quality and variety, plus ease of accessing the store or products in-store. Many participants described how they made unintended food selections as a result of prominent placement of unhealthy products in supermarkets, even if they adopted more conscious approaches to food shopping (i.e. written or mental lists). Participants described healthy eating as a personal responsibility, but some stated that governments and supermarkets could be more supportive. Conclusions This study highlighted that in-store environments can undermine intentions to purchase and consume healthy foods. Creating healthier supermarket environments could reduce the burden of personal responsibility for healthy eating, by making healthier choices easier. Future research could explore the interplay of personal, societal and commercial responsibility for food choices and health status.